MARKET DYNAMICS AND POLICY SYNERGY: ALIGNING GREEN BUSINESS WITH SUSTAINABLE ENVIRONMENTAL GOVERNANCE - Anggi Pratiwi Sitorus; Meisya Syahinda Auni; Aura Afifah Shaliha; Roganda Julyanto Raja Guk-Guk; Frisca Nabilla (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
This research aims to identify strategic directions and policy implications for improving alignment between green business and sustainability policy implementation in Indonesia and other developing countries. The research method used is a thematic synthesis of academic literature, international reports, and national policy documents related to green business practices, ESG, and market-policy integration. The results indicate that strengthening market-policy integration through an integrated data infrastructure and institutionalizing ESG as a regulatory standard are key to success. A National Green Market Intelligence System and mandatory ESG compliance can improve transparency, policy effectiveness, and business competitiveness. The study's conclusions confirm that alignment between market mechanisms, policies, and ESG governance forms a Market-Policy Alignment framework that supports sustainable economic growth, regulatory compliance, and environmental management, and encourages an inclusive transition towards the Green Economy 2045 vision.